Patterns of host-parasite associations in tropical lice and their passerine hosts in Cameroon - Gajdošová, Magdalena; Sychra, Oldřich; Kreisinger, Jakub; Sedláček, Ondřej; Nana, Eric Djomo; Albrecht, Tomáš; Munclinger, Pavel (Ecology and evolution, 2020)
Coevolutionary processes that drive the patterns of host-parasite associations can be deduced through congruence analysis of their phylogenies. Feather lice and their avian hosts have previously been used as typical model systems for congruence analysis; however, such analyses are strongly biased toward nonpasserine hosts in the temperate zone. Further, in the Afrotropical region especially, cospeciation studies of lice and birds are entirely missing. This work supplements knowledge of host-parasite associations in lice using cospeciation analysis of feather lice (genus Myrsidea and the Brueelia complex) and their avian hosts in the tropical rainforests of Cameroon. Our analysis revealed a limited number of cospeciation events in both parasite groups. The parasite-host associations in both louse groups were predominantly shaped by host switching. Despite a general dissimilarity in phylogeny for the parasites and hosts, we found significant congruence in host-parasite distance matrices, mainly driven by associations between Brueelia lice and passerine species of the Waxbill (Estrildidae) family, and Myrsidea lice and their Bulbul (Pycnonotidae) host species. As such, our study supports the importance of complex biotic interactions in tropical environments.
Keywords: host–parasite associations; passerines; cospeciation; feather lice; host switching; tropical ecology